Correction of Mixed Astigmatism: Arcuate Keratotomy Versus Excimer Laser - Rodríguez Rodríguez, Mario (1998)
OBJECTIVE: To compare the results obtained throughout the use of two different surgical techniques (Excimer Laser vs. arcuate keratotomy) for correction of mixed astigmatism. MATERIAL AND METHODS: A retrospective study of 110 arcuate keratotomy procedures in mixed astigmatisms and 68 excimer laser procedures, performed at OftalmoSalud Ophthalmology Institute, Lima - Peru, was made. RESULTS: Very similar results, when astigmatism was not higher than 3 dioptries and hypermetropy was not higher than 2 dioptries, were obtained. CONCLUSIONS: Today, the most confident surgical technique for correction of mixed astigmatism is photoreactive keratotomy performed in two steps.